Problem-based learning versus teaching personal social responsibility: efforts to improve students' responsible attitudes and learning motivation - Perdima, Feby Elra; Suwarni; Malema, Makhaya Johannes; Khamraeva, Zukhro Bahadirovna; Setiawan, Edi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: The application of learning models in physical education (PE) had increased significantly, but there was limited research that investigated the comparison of two different learning models in improving students’ responsibility attitudes and learning motivation at the university level. Research Objectives: This study aims to investigate the effects of problem-based learning (PBL) and teaching personal social responsibility (TPSR) models towards the improvement of students' responsibility attitudes and learning motivation. Methods: This study applied a true experiment method with a pretest-posttest control group design. There were 30 students who participated at the university level who were allocated into PBL [male: n = 10; female: n = 5] and TPSR (male: n = 10; female: n = 5). The PBL and TPSR programmes were implemented for 12 weeks. The responsibility attitudes and learning motivation were measured in the pre- and post-test. Finding/Results: The findings in this study indicated that the PBL and TPSR models had a significant positive effect on improving responsibility attitude and learning motivation. However, a higher increase was found in the TPSR group compared to PBL. Conclusion: Thus, both learning models, PBL and TPSR, can be used as a solution to improve the responsibility attitudes and motivation among students during physical education learning.